Spectrality in Margaret Atwood’s “Death by Landscape” (1990) - Gibert, Teresa (Miscelánea: A Journal of English and American Studies, 2018)
This article explores how Margaret Atwood engages with the literary trope of spectrality through the ghost of Lucy in “Death by Landscape” (1990), an enigmatic short story which can be fruitfully analyzed in the light of both the author’s critical writings and the spectropoetics introduced by Jacques Derrida. As an outstanding example of the Canadian Gothic, this brief narrative not only addresses the universal concerns of death and bereavement, but also raises more specific key issues, including present-day human relationships with the natural environment and the perception of geographical spaces as symbolic sites. Lucy’s ghostly presence haunting Lois draws special attention to the noxious effects of the modern appropriation of Native-American cultures, a controversial topic illustrated by the Indian-themed summer camp where Lucy mysteriously disappears and by her naïve friend Lois’s explicit desire “to be an Indian”. Additionally, Atwood’s short story evokes the physical displacement due to colonial expansion and recalls the ensuing social dislocation of the decimated Native populations, eventually almost erased from the actual and imaginary landscapes of North America.
Keywords: spectrality; ghost stories; Canadian Gothic; death; natural environment